Radical Scavenging Activity and Cytotoxicity of Euphorbia hirta L. growing in Egypt - Riham Omar Bakr; Mohamed Abd El-Aziz El-Raey; Christin Nader Farouk; Hadil Emad Ahmed; Ola Mohamed El-Said (International Journal of Phytomedicine, 2012)
Euphorbia hirta L. (asthma weed, pill bearing spurge), is one of the most important species of Euphorbiaceae indigenous to Egypt and widely used in folk medicine. It was the subject for many phytochemical and biological studies but correlation between phytoconstituents and biological activities were not well studied. The aim of the present study was to correlate the antioxidant and cytotoxic activities against two of the most important health problems in Egypt with the main constituents in E. hirta (phenolic and flavonoid). The different fractions obtained from successive extraction of E. hirta were screened for their radical scavenging ability using 1,1-diphenyl-2-picryl hydrazine (DPPH) test in addition to cytotoxicity using Sulforhodamine B (SRB) assay against liver (Huh-7) and lung (A-549) cell carcinoma. Phenolic and flavonoid contents were estimated using colorimetric assays (Folin-Ciocalteu and aluminum chloride assays respectively). Ethyl acetate (EtOAc) fraction appeared as potent radical scavenger (IC50 5.4±0.65 µg/ml and IC90 11.9±0.84 µg/ml) and had the highest potency against Huh-7 (IC50 36.7±1.02 µg/ml) and A-549 (IC50 114.4 ±0.78 µg/ml) cancer cell lines. These results are attributed to the highest flavonoid concentration (23±1.06 mg/g quercetin equivalent) in EtOAc fraction in addition to high content of phenolics (88.9 ±0.57 mg/g gallic acid equivalent). Further studies are necessary to isolate and identify the ethyl acetate’s bioactive compounds and evaluation of their biological activities.